IMPLEMENTASI UNDANG-UNDANG NOMOR 12 TAHUN 2022 TENTANG TINDAK PIDANA KEKERASAN SEKSUAL PADA KASUS KEKERASAN SEKSUAL DI KOTA AGUNG PROVINSI LAMPUNG - Utami, Dwi Astuti (SINERGI : Jurnal Riset Ilmiah, 2025)
The implementation of Sexual Violence Act Number 12 of 2022 which has been in effect since the date of its enactment should ideally be followed up by law enforcement by implementing the Sexual Violence Act in handling sexual violence crimes, but in reality this has not been implemented optimally. The problems of this research are: (1) How is Act Number 12 of 2022 implemented in cases of sexual violence in Kota Agung, Lampung Province? (2) How is the effectiveness of implementing Act Number 12 of 2022? The type of research used is normative as doctrinal legal research or theoretical legal research. Data collection was carried out by means of literature study. Data analysis is done descriptively qualitatively.  The results of the study show: (1) The implementation of Act Number 12 of 2022 in cases of sexual violence in Kota Agung, Lampung Province has not been implemented optimally, this is due to the lack of optimal understanding of the substance regulated in the Sexual Violence Act, so that law enforcers prefer to use various other laws that are already commonly applied. In addition, the implementation of the provisions and changes in the Sexual Violence Act is not yet ready, such as the absence of a Government Regulation regarding the Act Number 12 of 2022 when handling cases of sexual violence, there are no implementing instructions and technical instructions from the institution, so that law enforcers are more comfortable implementing the rules that already exist. (2) The effective way to implement Act Number 12 of 2022 is to socialize the Sexual Violence Act to law enforcers, related stakeholders and the wider community. Establishing technical regulations for implementing the Sexual Violence Act as an operational basis for law enforcers in implementing the Sexual Violence Act and establishing an Integrated Criminal Justice System for Handling Sexual Violence Act.  The conclusion of the study shows that Act Number 12 of 2022 in cases of sexual violence has not been optimally implemented by law enforcers. To the government to implementation of all implementing regulations of the Sexual Violence Act and optimizing socialization of the Sexual Violence Act